Characterization of the complete mitogenome of a land leech, Haemadipsa crenata Ngamprasertwong (Arhynchobdellida: Haemadipsidae) - Mo Wang; Xiangrong Tong; Yuan Su; Fanming Meng; Zichao Liu (Mitochondrial DNA. Part B. Resources, 2021)
Land leeches of genus Haemadipsa (Family Haemadipsidae) are widely distributed in South East Asia. Haemadipsa crenata Ngamprasertwong is a blood-feeding species firstly reported from Thailand. A complete mitochondrial genome of H. crenata was characterized in this study for further genetic exploration on land leech. The reads were assembled into a circular mitogenome of 14,725 bp in length. The AT content of H. crenata mitogenome is 76.79%. The annotated mitogenome contains 22 tRNAs, 2 rRNAs, and 13 protein-coding genes (PCGs), and the structure of PCG open reading frames was confirmed. Finally, the phylogenetic relationship of H. crenata and other leech species were reconstructed using mitogenomes.